Differences in Antioxidant activity of two varieties on pine nut seeds grown in Portugal - Ribeiro, Mariana M. (2019)
Antioxidants are a field of food science and nutrition which is under close attention: Maintaining homeostasis; Protecting cellular components; Reducing oxidative stress. Food can be a source of several compounds with antioxidant activity. It is known that pine nut seeds are important sources of various antioxidant compounds.